FAMILY STRUCTURE CORRESPONDING WITH DELINQUENT BEHAVIORS - Santiago, Miranda (2019)
The significance of this research study is to identify if an adolescences family structure impacts their developmental behaviors. The research design for this study was a quantitative design. The data analysis includes the independent variable (IV) and dependent variable (DV). For this study the IV was family structure and the DV in this study was delinquent behaviors. The findings suggest that during the pre-assessment tool researchers found there was no significance between family structure and delinquent behaviors. However, during the post assessment researchers found that there was significance between family structure and delinquent behavior. Although this study did not find significance during the pre-assessment, there were significant findings in the post-assessment that demonstrated that social workers should continue to consider family dynamics when assessing adolescents’ developmental behaviors